Dualisme Penanganan Anak Pelaku Kekerasan Seksual dalam Perspektif UU SPPA dan UU Perlindungan Anak - Depasbond Vijaya; Tri Andrisman; Sri Riski (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon of increasing sexual violence crimes committed by children in Indonesia poses a dilemma for law enforcement. Children as perpetrators are legally responsible subjects, but they still require special protection. This study analyzes the dualism in the regulations of Law No. 11 of 2012 on the Juvenile Criminal Justice Sistem (UU SPPA) and Law No. 35 of 2014 on Child Protection. A normative and empirical legal approach is used to assess the substance, philosophy, and implementation of both laws. The results indicate inconsistencies in the application of restorative justice principles (diversion) and repressive sanctions. It is recommended that regulations be harmonized and the capacity of law enforcement officials be strengthened to achieve a fair and recovery-oriented sistem.